Sociological Analysis of the Cultural and Artistic Taste (Case Study: Citizens of Ahwaz) - Amir Farokhvandi; Hossein Aghaghani Marsa; Mehrdad Navabakhsh; Soroush Fathi (توسعه اجتماعی)
In the history of culture and art, there have been diverse approaches to Taste, Some have a essentialistic approach and others have given a relativistic concept of taste. This research has been done with the aim of measuring the cultural and artistic taste of Ahwaz citizens, studying its dimensions and factors affecting it sociologically. By interviewing the most important indexes related to cultural and artistic taste were identified and then, using the Survey method, citizens of Ahwaz were studied. The results of this study show that the rate of interest of 1 percent of respondents to the use of cultural and artistic indexes is very low, 13/1 percent is Lowe, 41/3 percent is average, 38/1 percent is high and 6/5 percent is too high. Among the diverse cultural and artistic indexes, Ahwaz citizens are the most interested in music and have the least interest to hear radio programs. By testing the research hypothesis, it was found that all 7 variables studied, included gender, type of job, ethnicity, educational level (academic education and other types of education), economic capital, cultural capital and Socioeconomic class, are factors affect on cultural and artistic tastes of Ahwaz citizens.